2016
DOI: 10.1177/0962280216657376
|View full text |Cite
|
Sign up to set email alerts
|

Semiparametric models for multilevel overdispersed count data with extra zeros

Abstract: This study proposes semiparametric models for analysis of hierarchical count data containing excess zeros and overdispersion simultaneously. The methods discussed in this paper handle nonlinear covariate effects through flexible semiparametric multilevel regression techniques. This is performed by providing a comprehensive comparison of semiparametric multilevel zero-inflated negative binomial and semiparametric multilevel zero-inflated generalized Poisson models under the real and simulated data. An EM algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…This is an improvement of the joint modeling of longitudinal zero-inflated count and survival model, as Feng and Zhu 27 and Mahmoodi et al. 26 used only the truncated power basis for modeling the longitudinal count response with extra zeros.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an improvement of the joint modeling of longitudinal zero-inflated count and survival model, as Feng and Zhu 27 and Mahmoodi et al. 26 used only the truncated power basis for modeling the longitudinal count response with extra zeros.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of longitudinal zero-inflated count data modeling, Mahmoodi et al. 26 and Feng and Zhu 27 use truncated power series for taking into account the non-linear effect on the response variable and the Monte Carlo EM for parameter estimation. We use a hurdle model under Poisson and negative binomial distributional assumption for zero-inflated count data.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ignoring or misdiagnosing the effect of these variables will not only bias the estimate of the effect, it will also make the effect appear meaningless. In this regard, generalized additive models (GAMs) have been extended for handling nonlinear associations for various outcomes including survival outcome (time-to-event) 15 25 . Leblanc et al, showed that the average error in the Cox model with an inappropriate functional form is three times higher than in a model with a non-linear functional effect form 17 .…”
Section: Introductionmentioning
confidence: 99%